Improved Beer Production Technology Using Unmated Raw Materials Obtained From Jerusalem - Rustambekova F.F (Genius Journals, 2024)
The article discusses an improved technology for the production of non-alcoholic beer using unmalted raw materials obtained from non-traditional Jerusalem artichoke raw materials. The author's work using new technology has produced products such as powder, concentrate, and syrup from the tuber part of Jerusalem artichoke, cultivated in Uzbekistan. These products were used in the preparation of beer. The main task of adding pre-prepared Jerusalem artichoke powders to the wort is to obtain different types of beer (also for dark and light), which will contain active natural values due to the enrichment of beer with native substances, including inulin, trace elements and other substances.
Keywords: Classic brewing method; mash; cooking with hops; non-traditional raw materials